Impact of climate variation on agricultural productivity and food security in rural India - Ajay Kumar; Pritee Sharma (Kiel Institute for the World Economy (IfW), 2013)
This research paper analyzes the impact of climate change on agricultural productivity in quantity terms, value of production in monetary terms and food security in India. The study undertook state wise analysis based on secondary data for the duration of 1980 to 2009. Climate variation affects food grain and non-food grain productivity and both these factors along with other socioeconomic and government policy variables affect food security. Food security and poverty are interlinked with each other as cause and effect and vice versa, particularly, for a largely agrarian economy of India. Regression results for models proposed in this study show that for most of the food grain crops, non-food grain crops in quantity produced per unit of land and in terms of value of production climate variation cause negative impact. The adverse impact of climate change on the value of agricultural production and food grains indicates food security threat to small and marginal farming households. The state wise food security index was also generated in this study; and econometric model estimation reveals that the food security index itself also gets adversely affected due to climatic fluctuations.
Keywords: Q18; Q54; P34; 330; climate change; food grain and non-food grain productivity; value of production; food security index (FSI); poverty